Towards the maturity stage an insight into the performance of French technopoles - Chorda, Isidre March
This study contains an insight into the current situation exhibited, in France, by a set of territorialized initiatives known as technopoles, as a way of learning valuable lessons about similar initiatives and projects still in their preliminary stages and prior to their full launching process.
A major goal in most technopoles lies in pushing stronger ties and smoother synergies, leading to the exchange of skills and competences between the tenants located in these sites and the local and regional scientific, technical and economic infrastructure.
Basically promoted by regional and local governments, the technopole phenomenon mushroomed across France in the second half of the 1980s. However, a generation of new technological poles in the 1990s has started to slow down, resulting from a more critical view of the viability and actual impact attributable to these instruments of policy.
This paper gathers the main conclusions arising from an empirical study concerning the technopolitan experiences in five metropolitan areas. Four are French : Lyon metropolis, District of Montpellier, District of Nantes, Ile de France Sud region. The last area is the new Belgian town of Louvain-la-Neuve, strongly driven by its University. We hope these results will serve as a useful guide to new technopolitan sites inspired by the French technopoles.
Whilst the growth of technopoles in France during the 1980s was very high, this growth had started to slow down in the 1990s and the writer examines their performance in five metropolitan areas.
Keywords: Technopoles--France.